2014
DOI: 10.1111/obr.12189
|View full text |Cite
|
Sign up to set email alerts
|

Fish or n3‐PUFA intake and body composition: a systematic review and meta‐analysis

Abstract: Obesity is a major public health issue and an important contributor to the global burden of chronic disease and disability. Studies indicate that fish and omega-3 polyunsaturated fatty acids (n3-PUFA) supplements may help prevent cardiovascular and metabolic diseases. However, the effect of fish oil on body composition is still uncertain, so we performed a systematic review of randomized controlled trials and the first meta-analysis on the association between fish or fish oil intake and body composition measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 72 publications
7
73
4
2
Order By: Relevance
“…In an experimental trial, fish oil-fed rats presented a 150% higher amount of peroxisome enzymes and lower hepatic triglyceride content when compared to safflower oil-fed rats [41]. These findings may elucidate the negative correlation between n-3 PUFA intake and BMI found in this study, which has also been reported in a study with fish or fish oil consumption that resulted in bigger weight loss and decreased BMI when comparing with the control group [42].…”
Section: Discussionsupporting
confidence: 67%
“…In an experimental trial, fish oil-fed rats presented a 150% higher amount of peroxisome enzymes and lower hepatic triglyceride content when compared to safflower oil-fed rats [41]. These findings may elucidate the negative correlation between n-3 PUFA intake and BMI found in this study, which has also been reported in a study with fish or fish oil consumption that resulted in bigger weight loss and decreased BMI when comparing with the control group [42].…”
Section: Discussionsupporting
confidence: 67%
“…Another example is the consumption of seafood and predatory fish, which are considered to contain high doses of health-hazardous substances including PFASs (31). At the same time, fish intake has been related to weight loss in randomized trials (32). Generally, seafood and fish are perceived as a more exclusive and expensive alternative to other sorts of meat thus consumed more frequently by individuals of higher socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…Results for agerelated changes are inconclusive: some authors reported increased CART mRNA expression ( Wolden-Hanson et al 2004), while others found no changes (Kappeler et al 2003). As shown by Sohn et al, testosterone may lower hypothalamic CART mRNA levels (Bender et al 2014). Therefore, there might be aging-related increase of CART activity in males.…”
Section: Cocaine-and Amphetamine-regulated Transcriptmentioning
confidence: 97%